THE IMPACT OF ARTIFICIAL INTELLIGENCE ON EDUCATIONAL LEADERSHIP: THEORETICAL FRAMEWORKS FOR MEASUREMENT AND EVALUATION - PARAMOLE, Oyeronke Christiana (Jurnal Saintifik (Multi Science Journal), 2025)
The integration of artificial intelligence (AI) in educational leadership presents both opportunities and challenges, prompting the need for a comprehensive understanding of its implications. This research explores how AI technologies can enhance decision-making, improve student outcomes and address ethical considerations within educational settings. Employing a qualitative case study approach, the research examines specific instances of AI implementation in various educational institutions including Georgia State University and San Diego Unified School District. Data collection involved document analysis and observations of AI tools in action. Thematic analysis was utilized to identify patterns and insights related to the effectiveness of AI in educational leadership. The findings reveal that AI tools significantly enhance data-driven decision-making, leading to improved student engagement and retention rates. Notably, the research highlights the importance of ethical considerations, such as data privacy and equity in access to AI technologies. The study concludes that while AI holds transformative potential for educational leadership, it necessitates a shift in leadership practices and frameworks to accommodate its complexities. Educational leaders must prioritize professional development, stakeholder engagement, and the establishment of ethical guidelines to ensure responsible AI integration. Overall, this research contributes valuable insights into the practical applications of AI in education, emphasizing the need for ongoing dialogue and adaptation as technology continues to evolve